Analysis of the Efficiency of Using a Tripod-Mounted Clinometer in Vertical Structure Measurement - Ridwan, Ridwan; Haedar, Ahmad Wahidiyat; Aprianti, Dwi Wahyuni; Ahmad, Irma Aswani (Indonesian Journal of Fundamental Sciences, 2025)
Abstract. This study aims to evaluate the efficiency and accuracy of tripod-mounted clinometers in comparison with handheld clinometers for vertical structure measurements. A comparative quantitative experimental approach was employed, involving 40 measurement trials conducted on a multistory building with a known control height of 12.832 meters. The collected data were analyzed using descriptive and inferential statistics, with a paired-samples t-test at the 0.05 significance level. The findings reveal that the tripod-mounted clinometer produced an average measurement of 12.86 m, with a standard deviation of 0.12 m and a deviation of +0.03 m from the actual value. In contrast, the handheld clinometer yielded an average of 11.43 m, a standard deviation of 0.58 m, and a deviation of −1.40 m. Statistical testing confirmed a significant difference (p < 0.05) between the two instruments in terms of both accuracy and measurement efficiency. It can thus be concluded that the tripod-mounted clinometer demonstrates superior accuracy and efficiency, primarily due to its mechanical stability during angle observation. These findings underscore the critical role of stable mechanical design in enhancing the performance of field measurement instruments within geodetic and engineering applications